Taxonomic and phylogenetic characterizations reveal two new species and a new record of Simplicillium (Cordycipitaceae, Hypocreales) from the Mayao River Valley, Guizhou, China - Chen, Wan-Hao; Li, Dan; Shu, Hui-Lin; Liang, Jian-Dong; Han, Yan-Feng (Phytotaxa, 2024)
Simplicillium species are widely distributed and commonly found on various substrates or as a fungicolous fungi. In this research, three arthropod-associated specimens were collected. Two new species, Simplicillium neocoleopterorum and S. vallense, and a new record of S. formicae in China, were isolated, established and described according to a multilocus phylogenetic analysis and their morphological characteristics.